2017
DOI: 10.1038/s41467-017-01217-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of high-grade serous ovarian carcinoma with and without associated serous tubal intra-epithelial carcinoma

Abstract: Many high-grade serous carcinomas (HGSCs) of the pelvis are thought to originate in the distal portion of the fallopian tube. Serous tubal intra-epithelial carcinoma (STIC) lesions are the putative precursor to HGSC and identifiable in ~ 50% of advanced stage cases. To better understand the molecular etiology of HGSCs, we report a multi-center integrated genomic analysis of advanced stage tumors with and without STIC lesions and normal tissues. The most significant focal DNA SCNAs were shared between cases wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
144
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(164 citation statements)
references
References 57 publications
7
144
0
Order By: Relevance
“…Because molecular profiling studies in HGSC are hindered by intrapatient heterogeneity , we sought to analyze multisite tumor samples from each patient. In agreement with previous reports, we found that global expression profiles of tumors do not differentiate between HGSC‐STIC and HGSC‐NOSTIC nor is there any association between HGSC‐STIC and TCGA molecular subtypes . Moreover, our analysis suggests that tumor samples taken from multiple sites from a single patient may exhibit molecular profiles that associate with different representative TCGA molecular subtype groupings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Because molecular profiling studies in HGSC are hindered by intrapatient heterogeneity , we sought to analyze multisite tumor samples from each patient. In agreement with previous reports, we found that global expression profiles of tumors do not differentiate between HGSC‐STIC and HGSC‐NOSTIC nor is there any association between HGSC‐STIC and TCGA molecular subtypes . Moreover, our analysis suggests that tumor samples taken from multiple sites from a single patient may exhibit molecular profiles that associate with different representative TCGA molecular subtype groupings.…”
Section: Discussionsupporting
confidence: 92%
“…We speculate that the difference between this study and Ducie et al results from a combination of several factors including; utilization of tumor samples from multiple sites per patient, a more homogenous patient population (i.e. stage 3/4 only, exclusion of primary peritoneal diagnosis, single institution), and batch adjustment to combine separate analyses.…”
Section: Discussionmentioning
confidence: 64%
“…We found that STICs displayed higher TET1 expression, compared to NFTEs (Figure A). Moreover, analysis of RNA‐seq data demonstrated higher transcript expression of TET1 in HGSOCs than in NFTE (Figure B). Likewise, immunohistochemistry showed undetectable to very low TET1 immunoreactivity in NFTE, but TET1 upregulation in HGSOCs (Figure C–F).…”
Section: Resultsmentioning
confidence: 96%
“…Recent studies strongly support that serous ovarian cancer can originate from the fallopian tube epithelium (FTE) with evidence from mouse models and genetic evolutionary studies (Ducie et al, 2017;Kim et al, 2012;Labidi-Galy et al, 2017;Perets et al, 2013). Previous work reported that the FTE is composed of PAX8 positive secretory, TUBB4 positive ciliated and CD44 positive basal cells (Clyman, 1966).…”
Section: Introductionmentioning
confidence: 92%